Content analysis of clinical indicators for Impaired gas exchange - Lívia Maia Pascoal; Marcos Venícios de Oliveira Lopes; Viviane Martins da Silva; Camila Maciel Diniz; Marília Mendes Nunes; Vanessa Emille Carvalho de Sousa Freire; Beatriz Beltrão Amorim (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To analyze the relevance of clinical indicators and the clarity and precision of conceptual and operational definitions of the diagnosis Impaired gas exchange. Methods Content analysis, by 39 nurse judges, divided into the phases of conceptual definition of the phenomenon of interest, construction of the structure of the phenomenon of interest and analysis of the judges on the built structure. Results From the 22 indicators, 21 were considered relevant Impaired gas exchange. The indicators that obtained absolute relevance were Cyanosis, Hypercapnia, Hypoxemia and Tachycardia. The indicator Headache upon waking did not show any statistically significant relevance for the diagnosis. All conceptual and operational definitions were clear and precise. Conclusion The indicators listed for Impaired gas exchange were relevant to the phenomenon, except Headache upon waking because it does not correspond to a safe manifestation to identify the diagnosis, according to the analysis of the judges. Each conceptual and operational definition was adequate for its indicator.